Non-axisymmetric dynamic response of buried orthotropic cylindrical shells under moving load - Singh V.P.; Dwivedi J.P.; Upadhyay P.C. (My University, 2025)
The dynamic response of buried pipelines has gained considerable importance because these pipelines perform vital role in conducting energy, water, communication and transportation. After realizing the magnitude of damage, and hence, the human uncomfort and the economical losses, researchers have paid sincere attention to this problem. A number of papers have appeared in the past which discuss the different aspects of the problem. This paper presents a theoretical analysis of non-axisymmetric dynamic response of buried orthotropic cylindrical shell subjected to a moving load along the axis of the shell. The orthotropic shell has been buried in a homogeneous, isotropic and elastic medium of infinite extent. A thick shell theory including the effects of rotary inertia and shear deformation has been used. A perfect bond between the shell and the surrounding medium has been assumed. Results have been obtained for very hard (rocky), medium hard and soft soil surrounding the shell. The effects of shell orthotropy have been brought out by varying the non-dimensional orthotropic parameters over a long range. Under these conditions the shell response is studied in axisymmetric mode as well as in the flexural mode. It is observed that the shell response is significantly affected by change in orthotropic parameters and also due to change of response mode. It is observed that axial deformation is large in axisymmetric mode as compared to that in flexural mode.